Basic needs support and achievement emotions in daily research of life scientists considering academic positions - Meuleners, Julia S.; Neuhaus, Birgit J.; Eberle, Julia (Frontiers in Education, 2022)
Emotions are a crucial factor in daily research of academic staff and, accordingly, affect scientific progress. Already before but especially during the COVID-19 pandemic, the strong connection between working conditions and work-related emotional states as antecedents for mental health of academic staff gained more and more attention. However, in depths investigations of researchers’ emotions in academia are still rare. In the highly competitive field of academia, experiencing the working environments as supportive may be an important influential factor for researchers’ emotions. On a structural level, academic positions may also be tied to different emotional experiences. Taking a Self-Determination Theory approach, we therefore investigate, whether a basic need-supportive environment (regarding perceived competence and autonomy support, and social relatedness to the scientific community) and the academic position (research assistants without leading responsibility and principle investigators with leading responsibility) predict activity-related achievement emotions (enjoyment, anger, frustration, and boredom) during daily research activities. However, measurements on basic needs support and achievement emotions tailored to the specific academic research context are lacking. Therefore, this study is aimed at developing fitted scales on these constructs. In a cross-sectional survey, we questioned N = 250 life scientists in 13 German universities. Results of multiple linear regression analyses suggest that supportive environments in academia were positively associated to the level of experienced enjoyment and negatively to the level of experienced frustration. Surprisingly, social relatedness to the scientific community does not affect frustration. Principle investigators report a more favorable emotional pattern with higher levels of enjoyment than research assistants. However, the level of experienced frustration was not affected by the academic position. The scales on anger and boredom seemed not to differentiate emotional experiences on these two negative achievement emotions in the research context accurately. Therefore, we needed to exclude anger and boredom from analyzes. Further research on these achievement emotions is needed. We discuss our findings on enjoyment and frustration and derive both theoretical and practical implications, taking an international and interdisciplinary perspective.